Vertical Distribution and Flux of Nutrients in the Sediments of the Mangrove Reclamation Region of Muara Angke Kapuk, Jakarta - Purwiyanto, Anna Ida Sunaryo; Prartono, Tri; Koropitan, Alan Frendy (UI Scholars Hub, 2012)
The reclaimed mangrove estuary in Muara Angke Kapuk is a reclaimed area that has not evaded the impacted of pollution and waste in the areas surrounding Cengkareng, Jakarta. This is apparent from the fact that almost all sediments under the mangrove trees are buried under heaps of plastic trash. However, the reclaimed region still has variety of organism, which indicating that the region still has an internal carrying capacity, especially nutrients from sediment. The purpose of this research was to examine the condition of sediment nutrients in this mangrove reclamation region. The research was conducted by taking water samples using a modification of the stratified cup at a sediment depth of 0-15 cm with depth intervals of 2.5 cm, and taking sediment samples using the sediment ring. Pore water samples were measured for dissolved oxygen (DO) and concentrations of ammonia, nitrite, nitrate, and phosphate. Sediment samples were used to obtain porosity values. The data obtained is used to make vertical concentration profiles and analysis of vertical nutrient flux. Vertical nutrient flux analysis was performed with the aid of QUAL2K software version 2.11. The results showed different vertical distributions and flux of nutrients, where influx for ammonia and phosphate and an increase in line with increasing sediment depth, while nitrate efflux and a decreased concentration. The flux calculation of nitrite as transitory nutrient was not done, but the concentration decreased after a depth of 2.5 cm. This indicates that the high contamination on the surface does not prevent the natural chemical processes so the reclaimed region can still provide nutritional support for its organism.